2022
DOI: 10.1093/intimm/dxac006
|View full text |Cite
|
Sign up to set email alerts
|

In silico analyses and experimental validation of the MHC class-I restricted epitopes of Ebolavirus GP

Abstract: Ebolavirus (EBOV) causes an extremely high mortality and prevalence disease called Ebola virus disease (EVD). There is only one glycoprotein (GP) on the virus particle surface, which mediates entry into the host cell. MHC class-I restricted CD8 + T cell responses are important antiviral immune responses. Therefore, it is of great importance to understand EBOV GP-specific MHC class-I restricted epitopes within immunogenicity. In this study, computational approaches were employed to predict the dominant MHC clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…It is universally acknowledged that the MHC class II presentation is required for the activation of Th cells and antiviral immunoprotection [19], yet it has rarely been reported on EBOV GP. Notably, a previous study confirmed the MHC class I presentation of EBOV GP by in silico analyses, exemplifying antigen immunoreactivity research [20]. In this study, the latest bioinformatics and traditional immunological methods were integrated to explore the pan-MHC-II-restricted immune reactivity of EBOV GP, and a series of selective epitopes were screened to aid in vaccine development.…”
Section: Introductionsupporting
confidence: 54%
“…It is universally acknowledged that the MHC class II presentation is required for the activation of Th cells and antiviral immunoprotection [19], yet it has rarely been reported on EBOV GP. Notably, a previous study confirmed the MHC class I presentation of EBOV GP by in silico analyses, exemplifying antigen immunoreactivity research [20]. In this study, the latest bioinformatics and traditional immunological methods were integrated to explore the pan-MHC-II-restricted immune reactivity of EBOV GP, and a series of selective epitopes were screened to aid in vaccine development.…”
Section: Introductionsupporting
confidence: 54%
“…Recently, immunologists followed this thought in glycoprotein epitope studies of Hantaan virus and Ebola virus, in which five or four affinity algorithms predicted MHC-I and MHC-II restricted epitopes, respectively, selecting epitopes with Rank ≤ 2% 3 or 2 times among toolkits. Strong cellular responses in enzyme-linked immunospot assays with corresponding epitopes validated the effectiveness of this strategy in infectious diseases such as viral hemorrhagic fever virus ( 29 31 ).…”
Section: Introductionmentioning
confidence: 94%
“…On this basis, another direction — further research on the impact of mutation sites — should also be taken into consideration. That is, the mutation site is brought into the original sequence to explore the impact of the mutation site on the affinity and immunogenicity of the specific epitopes ( 29 , 31 ). This analysis of the mutated sequences in silico predicts the approximate direction of evolutionary impacts on immunogenetic variation and deepens the understanding of pathogen conservation.…”
Section: Introductionmentioning
confidence: 99%
“…This also employs the use of subtractive proteomics techniques to design vaccine therapeutics against several organisms [ 26 ]. In several studies, similar in silico techniques were employed in order to propose potent vaccine candidates and to subsequently validate the vaccine candidates experimentally [ 27 , 28 , 29 ]. In a study, the authors performed a comparative analysis of Mycobacterium tuberculosis and identified major and HLA-promiscuous antigenic proteins and peptides which showed strong immunogenicity in in vivo and in vitro analysis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, the authors performed a comparative analysis of Mycobacterium tuberculosis and identified major and HLA-promiscuous antigenic proteins and peptides which showed strong immunogenicity in in vivo and in vitro analysis [ 29 ]. In another study, Liu et al predicted the MHC class-1 of Ebolavirus using in silico approaches, and subsequently, their anti-EBOV immune responses were confirmed by in vivo experiments [ 27 ].…”
Section: Introductionmentioning
confidence: 99%